2022
DOI: 10.3389/fcimb.2022.927193
|View full text |Cite
|
Sign up to set email alerts
|

Damage associated molecular patterns and neutrophil extracellular traps in acute pancreatitis

Abstract: Previous researches have emphasized a trypsin-centered theory of acute pancreatitis (AP) for more than a century. With additional studies into the pathogenesis of AP, new mechanisms have been explored. Among them, the role of immune response bears great importance. Pro-inflammatory substances, especially damage-associated molecular patterns (DAMPs), play an essential role in activating, signaling, and steering inflammation. Meanwhile, activated neutrophils attach great importance to the immune defense by formi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 229 publications
0
11
0
Order By: Relevance
“…During AP, injured PACs commonly release substances from the cell, comprising damage-associated molecular patterns (DAMPs), which trigger diverse immune cells’ recruitment (including neutrophils, monocytes, and macrophages) to the damaged area, inducing cell polarization and release of inflammatory factors and cytokines, thereby activating inflammatory cascade. …”
Section: Resultsmentioning
confidence: 99%
“…During AP, injured PACs commonly release substances from the cell, comprising damage-associated molecular patterns (DAMPs), which trigger diverse immune cells’ recruitment (including neutrophils, monocytes, and macrophages) to the damaged area, inducing cell polarization and release of inflammatory factors and cytokines, thereby activating inflammatory cascade. …”
Section: Resultsmentioning
confidence: 99%
“…It was found that NMAP patients had greater infiltration ratios of neutrophils and mast cells. Neutrophils were found to be critical in the development of AP, and treatment aimed at neutrophils significantly reduced tissue damage and prevented pancreatitis [ 39 , 40 ]. Mast cells also usually play a key role in the inflammatory reaction in AP [ 41 ], which is consistent with the results we obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Clarifying the endogenous mechanisms underlying AP progression could help to clinically treatment and improve prognosis. Besides the classical role of neutrophils, numerous findings suggest that neutrophil-derived NETs play an important role in the pathophysiology of AP ( 8 , 25 27 ). Based on the role of P-selectin in neutrophil functions, our study focused on the relationship between the highly expressed P-selectin and NETs in AP and found that in human neutrophils P-selectin is an important stimulus of NETs formation, which is consistent with the findings of Etulain et al.…”
Section: Discussionmentioning
confidence: 99%